2017
DOI: 10.1111/cup.12886
|View full text |Cite
|
Sign up to set email alerts
|

Three unusual histopathological presentations of angiolymphoid hyperplasia with eosinophilia

Abstract: Angiolymphoid hyperplasia with eosinophilia (ALHE) is a poorly understood benign vasculoproliferative disorder. Histopathologically, the lesions are composed of a dermal or subcutaneous proliferation of blood vessels of varying sizes with plump and bland endothelial cells, which often show vacuolization and protrusion of the cytoplasm into the lumen. The vascular proliferation is admixed with a diffuse inflammatory infiltrate composed of lymphocytes, eosinophils and mast cells. Lymphoid follicles with germinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The disease mainly occurs in Asia, with a slightly higher incidence in male patients compared with that in female patients and a wide range of age of onset (8). The tumor, which is mainly distributed in the head and neck, and more specifically around the ear and auricle, is presented as dermal papules or nodules, commonly accompanied by itching and scratching; therefore, the patients are prone to bleeding (9). The early stage of the disease is characterized by vascular proliferative lesions, while the late stage presents significant lymphoproliferative lesions, which needs to be differentiated morphologically from Kimura's disease (8,10).…”
Section: Discussionmentioning
confidence: 99%
“…The disease mainly occurs in Asia, with a slightly higher incidence in male patients compared with that in female patients and a wide range of age of onset (8). The tumor, which is mainly distributed in the head and neck, and more specifically around the ear and auricle, is presented as dermal papules or nodules, commonly accompanied by itching and scratching; therefore, the patients are prone to bleeding (9). The early stage of the disease is characterized by vascular proliferative lesions, while the late stage presents significant lymphoproliferative lesions, which needs to be differentiated morphologically from Kimura's disease (8,10).…”
Section: Discussionmentioning
confidence: 99%
“…6 When multiple, EHs usually appear grouped and may be confluent. Some clinical and histological findings indicate a reactive nature of EH, 1,7 such as history and evidence of previous inflammatory stimuli or trauma. However, the aetiology and pathogenesis of EH are still unclear.…”
Section: What Is the Translational Message?mentioning
confidence: 99%
“…A recent case report coexisting with peripheral T cell lymphoma explored the relationship to haematologic malignancy, which can exhibit eosinophilic dermatosis. In view of the variety of concomitant disease processes, the authors concluded that angiolymphoid hyperplasia with eosinophilia is more likely to be a reactive phenomenon than a true neoplasm 7 …”
Section: Figurementioning
confidence: 99%
“…In view of the variety of concomitant disease processes, the authors concluded that angiolymphoid hyperplasia with eosinophilia is more likely to be a reactive phenomenon than a true neoplasm. 7 Recently, it has been reported that THSD7A, a protein that causes membranous nephropathy, is upregulated by eosinophils in angiolymphoid hyperplasia with eosinophilia and that there is increased VEGF-A expression, especially in conditions that support the Th type 2 phenotype. The authors hypothesised that immune responses mediated by Th type 2 cells might link angiolymphoid hyperplasia with eosinophilia to membranous nephropathy.…”
Section: Case Lettermentioning
confidence: 99%